Assessing Governance Status: Learning from Community Forest User Groups, Nepal - Raut, Sameen; Upadhaya, Suraj; Godar Chhetri, Sagar; Joshi, Murari Raj (Journal of Forest and Natural Resource Management, 2020)
Community forestry practices have proven to be successful in forest resource conservation and utilization in Nepal. Nevertheless, inclusive decision-making processes and equitable benefit-sharing among each household pose significant challenges to the Community Forestry Users Groups (CFUGs). The four key elements of good governance: Participation, Transparency, Accountability, and Predictability, each with their four own local indicators, were employed to measure the governance status in two CFUGs: Bosan and Hattiban Mahila in Kathmandu district. We collected data through a questionnaire survey (n=95), focus group discussions, and key informant surveys. The results showed that the general status of governance in Bosan CFUG was 'Good' (43 out of a total attainable score of 64), whereas that of Hattiban Mahila CFUG was 'Medium'(32 out of a total attainable score of 64). Scores for Transparency, Accountability, and Predictability in Bosan CFUG managed by men and women alike were found to be higher than those of Hattiban Mahila CFUG, which was managed mostly by women. Both the CFUGs received the same score for good governance element: Participation. This study helps policymakers to formulate effective programs for CFUGs members to improve the governance system in such forestry user groups.